À volta do casamento do infante D. Pedro - Douglas Mota Xavier de Lima (Medievalista)
Having as basis the famous article written by António Joaquim Dias Dinis concerning D. Duarte’s marriage, it is proposed an approach of another connection equally important for the crown of Avis, the marriage of the infant D. Pedro from Portugal with D. Isabel of Urgel. Such consortium is analyzed in the context of the Iberian diplomatic relationships, especially between Portugal and Aragon, and of the matrimonial avisin politics of the first decades of the 15th century. Being traditionally seen as negative for the kingdom because of the disputes, for and during the regency, among D. Pedro and D. Leonor of Aragon, queen of Portugal and member of a rival family of the infant’s wife, the marriage is analyzed proposing a historiographical revision and a new reading of the documents about the Portuguese-Aragonese relationships from the 1420’s and 1430’s.